Analysis of Investor Reactions Comparison to Covid-19 Developments in ASEAN Capital Market - Kristanto, Patricia Frenio; Sumanti, Elvis (Jurnal Multidisiplin Madani, 2024)
The COVID-19 pandemic has had a major impact on various sectors, one of which is the capital market sector. Information and investors' observations of the COVID-19 phenomenon in their countries will encourage different market behavior when compared to the period before the COVID-19 pandemic in various countries. This study aims to examine the effect of the development of COVID-19 from early 2020 to mid-2022 on the ASEAN stock market represented by Indonesia, Malaysia, the Philippines, Singapore, and Thailand. The research design uses a quantitative approach and applies the regression data analysis method using a panel data regression model, using data on changes in COVID-19 cases, stock price index, and daily exchange rates obtained from the official website. Data processing was carried out using the STATA statistical tool. As a result of the research, it was found that each ASEAN country had different investor reactions to developments in COVID-19. This means that not all countries make the development of COVID-19 a factor that investors consider in making investment decisions, and there are other factors that influence investor reactions in the ASEAN capital market during the COVID-19 pandemic period